2022
DOI: 10.1002/mp.16124
|View full text |Cite
|
Sign up to set email alerts
|

High‐pitch, high temporal resolution, multi‐energy cardiac imaging on a dual‐source photon‐counting‐detector CT

Abstract: To measure the accuracy of material decomposition using a dualsource photon-counting-detector (DS-PCD) CT operated in the high-pitch helical scanning mode and compare the results against dual-source energyintegrating-detector (DS-EID) CT, which requires use of a low-pitch value in dual-energy mode. Methods: A DS-PCD CT and a DS-EID CT were used to scan a cardiac motion phantom consisting of a 3-mm diameter iodine cylinder. Iodine maps were reconstructed using DS-PCD in high-pitch mode and DS-EID in low-pitch m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…At the same dose, the higher photon efficiency leads to lower image noise [13], possibly shifting the threshold above which unacceptable decreases in image quality occur. Furthermore, the generated virtual monoenergetic images improve iodine contrast, which may allow better differentiation between cardiac vessels and tissue [18]. Only 5.4% of the included patients had a HR of 70 or more, and the highest recorded heart rate at the scan was 73.…”
Section: Discussionmentioning
confidence: 99%
“…At the same dose, the higher photon efficiency leads to lower image noise [13], possibly shifting the threshold above which unacceptable decreases in image quality occur. Furthermore, the generated virtual monoenergetic images improve iodine contrast, which may allow better differentiation between cardiac vessels and tissue [18]. Only 5.4% of the included patients had a HR of 70 or more, and the highest recorded heart rate at the scan was 73.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were brought to PCD-CT immediately after completion of their EID-CT scan. Photon-counting detector CT scans were acquired using a prospectively triggered dual-source high-pitch “Flash” protocol (“CardiacFlashSpiralAdultQuantumplus,” pitch = 3.2) 15 with 120-kV, CARE keV image quality level of 32, 0.25-second rotation time, 144 × 0.4-mm collimation (5.76-cm z -axis coverage), and a 55% starting phase.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 This provides brighter signal for low concentrations of high atomic number materials. With use of 2 x-ray tubes and 2 detectors (ie, a dual-source geometry) and a 0.25-second rotation time, cardiac multienergy imaging is possible with a temporal resolution of 66 ms. 6,15 In dual-source EID-CT scanners, the temporal resolution must be decreased to 125 ms if multienergy imaging capabilities are desired. In total, PCD-CT offers many advantages for quantitative imaging applications in the heart.…”
mentioning
confidence: 99%
“…In cardiac phantoms, this mode performs material decomposition with excellent geometric and quantitative accuracy, and motion robustness, due to improved temporal resolution and spatiotemporal registration. 20 A dynamic phantom study showed the possibility of 50% contrast reduction using low-energy VMI in this mode. 21 A thoracic CTA study using this mode showed significantly increased contrast-to-noise ratio (CNR) of low-energy VMI compared with conventional energy integrating detector (EID) CT at the same radiation dose.…”
mentioning
confidence: 96%
“…The first commercial dual-source (DS) PCD-CT (NAEOTOM Alpha; Siemens) has a novel high-pitch helical ME scan mode (Quantumplus), which enables a helical pitch up to 3.2 simultaneous to an ME acquisition at a temporal resolution of 66 milliseconds. In cardiac phantoms, this mode performs material decomposition with excellent geometric and quantitative accuracy, and motion robustness, due to improved temporal resolution and spatiotemporal registration 20 . A dynamic phantom study showed the possibility of 50% contrast reduction using low-energy VMI in this mode 21 .…”
mentioning
confidence: 97%